Ionic conductivity, ionic transport and electrochemical characterizations of plastic crystal polymer electrolytes - Zainuddin, Z.; Hambali, D.; Supa'at, I.; Osman, Z. (Springer Verlag (Germany), 2017)
In this work, the plastic crystal polymer electrolytes (PCPEs), composed of polyacrylonitrile (PAN), succinonitrile (SN) and lithium bis(trifluoromethane)sulfonimide (LiTFSI) were prepared. The concentrations of lithium salt were varied by weight percentage from 10 wt% to 50 wt%. The ionic conductivity of the PCPE films increases with the increase of lithium salt, where the highest value recorded is in the order of ~10−2 S cm−1. The temperature-dependence conductivity analysis shows that the PCPE films exhibit Arrhenius behaviour when subjected to the temperature range from 303 K to 343 K. The decrease in crystallinity was confirmed by X-ray diffraction (XRD) and Differential Scanning Calorimetry (DSC) analyses. The cationic transport number also increases with the increase of salt which corresponds well to their conductivity values. It is found that the films are electrochemically stable up to ~3.6 V as revealed by the linear sweep voltammetry (LSV) analysis. The cyclic voltammetry (CV) plots of the films shown no substantial change in the redox peaks which mean that the charge transfer reaction is reversible.